Kidding around Washington, D.C. : a young person's guide - Pedersen, Anne, 1949-; Finnell, Jim (Santa Fe, N.M. : J. Muir Publications ; New York : Distributed by Norton ; Bothell, WA : Distributed to the education market by the Wright Group, 1993)
A guidebook to Washington, D.C., surveying such areas as Capitol Hill, the Mall museums, monuments, parks, Georgetown, and nearby Virginia.
Includes index.
Keywords: Children -- Travel -- Washington (D.C.) -- Guidebooks -- Juvenile literature; Washington (D.C.) -- Guidebooks -- Juvenile literature; Washington (D.C.) -- Guides